Highly Oblique Lower‐Band Chorus Statistics: Dependencies of Wave Power on Refractive Index and Geomagnetic Activity. Issue 6 (16th June 2018) - Shi, R.; Mourenas, D.; Artemyev, A.; Li, W.; Ma, Q.
Abstract: We use 3 years of Van Allen Probes observations of highly oblique lower‐band chorus waves at low latitudes over L = 4–6 to provide a comprehensive statistics of the distribution of their magnetic and electric powers and full energy density as a function of wave refractive index N, L shell, and geomagnetic activity A E . We use the refractive index calculated either in the cold plasma approximation or in the quasi‐electrostatic (hot plasma) approximation and either observed wave electric fields or corrected wave electric fields accounting for the formation of a plasma sheath around antenna probes in a low‐density plasma. Approximate fits to the maximum refractive index and to the magnetic wave power profile of highly oblique waves are provided as a function of A E and L . Such fits should be useful for simulations of quasi‐linear electron diffusion induced by very oblique chorus waves. The magnetic wave power of these oblique waves remains elevated and roughly constant up to higher N values at lower L < 5 and during less disturbed periods A E ∗ <200 nT, likely due to the corresponding lower temperature of hot electrons injected from the plasma sheet, which leads to weaker thermal effects and Landau damping of these very oblique waves. The average energy density of lower‐band chorus waves is mainly distributed from N = 30–50 up to N = 150–300, mostly corresponding to highly oblique waves even at low magnetic latitudes. Key Points: A statistical study of highly oblique lower‐band chorus waves is performed based on Van Allen Probes observations Highly oblique wave magnetic power remains high and roughly constant from N 50 up to maximum values N 85–150 of wave refractive index The maximum value of the wave refractive index depends on L, MLT, and geomagnetic activity